Pengaruh Kewajiban Moral Dan Digitalisasi Layanan Pajak Terhadap Kepatuhan Wajib Pajak Dengan Nasionalisme Sebagai Pemoderasi - Sihar Tambun; Nurul Aulia Ananda (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to examine the effect of moral obligation and digitization of tax services on taxpayer compliance with nationalism as a moderator. The population used in this study are taxpayers who understand the process of reporting and paying taxes. The number of data is 100 respondents who are taken through a questionnaire using partial least squares (PLS) data analysis. Based on statistical tests, the results of the study show that Moral Obligations have no significant effect on taxpayer compliance. Digitization of Tax Services has a significant effect on Taxpayer Compliance. Nationalism has no significant effect on taxpayer compliance. Moral Obligations to Taxpayer Compliance if moderated by Nationalism have a significant effect. Digitizing Tax Services on Taxpayer Compliance if moderated with Nationalism does not have a significant effect